2023
DOI: 10.3389/fgene.2023.1027690
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonate lipoxygenases 5 is a novel prognostic biomarker and correlates with high tumor immune infiltration in low-grade glioma

Abstract: Objective: To investigate the prognostic value of arachidonate lipoxygenases 5 (ALOX5) expression and methylation, and explore the immune functions of arachidonate lipoxygenases 5 expression in low-grade glioma (LGG).Materials and Methods: Using efficient bioinformatics approaches, the differential expression of arachidonate lipoxygenases 5 and the association of its expression with clinicopathological characteristics were evaluated. Then, we analyzed the prognostic significance of arachidonate lipoxygenases 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Although previously Nathoo et al demonstrated that 5-LOX is highly expressed in high-grade astrocytomas [88], a comparison with our study cannot be performed considering that we analysed GBM in contrast with astrocytomas, without distinguishing between low-and high-grade astrocytomas. At transcriptional level, gene expression for ALOX5 was increased in both LGG and GBM in comparison to the normal counterpart, as previously already reported [86]. Data from publicly available datasets also showed a significant increase in CD3D, CD3E and SDC1 (CD138) expression in GBM compared to normal tissues, whereas the expression for the same genes was not significantly modulated in LGG when compared to controls indicating that their increased expression could be related to GBM pathogenesis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although previously Nathoo et al demonstrated that 5-LOX is highly expressed in high-grade astrocytomas [88], a comparison with our study cannot be performed considering that we analysed GBM in contrast with astrocytomas, without distinguishing between low-and high-grade astrocytomas. At transcriptional level, gene expression for ALOX5 was increased in both LGG and GBM in comparison to the normal counterpart, as previously already reported [86]. Data from publicly available datasets also showed a significant increase in CD3D, CD3E and SDC1 (CD138) expression in GBM compared to normal tissues, whereas the expression for the same genes was not significantly modulated in LGG when compared to controls indicating that their increased expression could be related to GBM pathogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, recent evidence showed that 5-LOX can contribute to a proliferative and pro-survival effect in glioma cells through a modulation of ERKs phosphorylation, Bcl-2/Bax signalling and via β-catenin-dependent pathway [74,75,85]. Moreover, a recent publication from Pan et al, showed a positive correlation between 5-LOX expression and tumour immune infiltration in LGG [86]. In line with these findings, we have reported a positive and significant correlation between the tissue expression of 5-LOX and GzmB in GBM samples.…”
Section: Discussionmentioning
confidence: 98%
“…Tumor-infiltrating immune cells play an essential role in tumor occurrence, progression, and metastasis. Thus, the immune score and stromal score were calculated using the ESTIMATE algorithm [ 25 ]. Besides, the TIMER and xCELL algorithms were adopted to evaluate the expression correlation of TTK with several immune cells.…”
Section: Methodsmentioning
confidence: 99%
“…PGK1 has been reported to promote cancer cell proliferation and migration in NSCLC through the downstream ERK/MCM4 pathway [94]. ALOX5 is generally downregulated in NSCLC [95], and its overexpression has been reported to be associated with tumor progression in gliomas [96].…”
Section: Nf-κb Target Genes' Activation Signature Following Irradiati...mentioning
confidence: 99%